2021
DOI: 10.1371/journal.pntd.0009387
|View full text |Cite
|
Sign up to set email alerts
|

“Kankasha” in Kassala: A prospective observational cohort study of the clinical characteristics, epidemiology, genetic origin, and chronic impact of the 2018 epidemic of Chikungunya virus infection in Kassala, Sudan

Abstract: Background The public health impact of Chikungunya virus (CHIKV) is often underestimated. Usually considered a mild condition of short duration, recent outbreaks have reported greater incidence of severe illness, fatality, and longer-term disability. In 2018/19, Eastern Sudan experienced the largest epidemic of CHIKV in Africa to date, affecting an estimated 487,600 people. Known locally as Kankasha, this study examines clinical characteristics, risk factors, and phylogenetics of the epidemic in Kassala City. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Of these, 119 studies were excluded because they were reviews (29), only reported on chikungunya (25), only reported on malaria or chikungunya mono-infection (21), were in vitro studies (12), performed assays (8), were case reports or case series (7), reported on malaria only (5), were animal studies (5), were systematic reviews (4), involved mathematical models (2), or did not have full text (1). Thus, 9 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] that met the eligibility criteria were included. Another study [ 23 ], identified from Google Scholar, was included.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 119 studies were excluded because they were reviews (29), only reported on chikungunya (25), only reported on malaria or chikungunya mono-infection (21), were in vitro studies (12), performed assays (8), were case reports or case series (7), reported on malaria only (5), were animal studies (5), were systematic reviews (4), involved mathematical models (2), or did not have full text (1). Thus, 9 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] that met the eligibility criteria were included. Another study [ 23 ], identified from Google Scholar, was included.…”
Section: Resultsmentioning
confidence: 99%
“…Another study [ 23 ], identified from Google Scholar, was included. Finally, 10 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were included for the qualitative and quantitative analyses ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations